Perencanaan Jadwal Distribusi Produk Radio Ke Wilayah Eropa dengan Metode Distribution Requirement Planning (DRP) di PT. X - Suryani, Bella; Mazwan, Mazwan; Zaqy, Sandi Yudha Barri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the distribution schedule planning of radio products to the European region using the Distribution Requirement Planning (DRP) method at PT. X. The main problem faced by the company is the high distribution costs due to the suboptimal delivery schedule. The study was conducted from February to May 2025 using a quantitative descriptive approach with primary data in the form of observations and interviews and secondary data including product demand, inventory, lead time, and logistics costs. The results of the analysis show that the DRP method is able to produce a more efficient distribution schedule with a total cost of Rp14,236,002, compared to the previous method of Rp29,764,423, or a savings of 52%. Thus, the implementation of DRP is proven to increase cost efficiency, optimize container capacity, and support the smoothness of the company's international distribution.